PENGARUH KECEMASAN MATEMATIS, PROBLEM STRESS MATEMATIKA DAN SELF-REGULATED LEARNING TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Tanisa Diva Aryani; Maylita Hasyim (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2018)
This study aims to analyze the influence of mathematical anxiety effects (X1), mathematical stress problems (X2) and self-regulated learning (X3) to the mathematics learning outcomes materials algebra operation (Y) in the seventh grade students of SMP Negeri 1 Tugu Trenggalek. This research uses a quantitative approach with causal causative research. Data analysis techniques in this study using multiple regression analysis. Based on the results of data analysis, simultaneously on multiple linear regression, there is influence between mathematical anxiety (X1), mathematical stress problem (X2) and self-regulated learning (X3) to the mathematics learning outcomes equal to 44,6% with regression equation Y = 100,365 + (- 0,619) X1 + (- 0.572) X2 + 0.449X3. Mathematical anxiety and mathematical stress problem negatively affects the mathematics learning outcomes, beside that self-regulated learning have a positive effect on mathematics learning outcomes.